Effectiveness Of Asthma Gymnastic On Asthma Status For Asthma Survivor - Suci Amanati; Didik Purnomo; Irawan Wibisono (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Asthma is a chronic inflammation disease in airways which is emit bronchus hyperactivity. Asthma is a worldwide trouble that influence at least 1-18% population in the entire world. Exercises is a non-pharmacological therapy which is can be applied for asthma case. Exercise that is applied on this research is asthma gymnastic and breathing exercise. The purpose from this research is to get the effect of asthma gymnastic and breathing exercise on asthma status for asthma survivor.The research method use eksperiment in madupahat community in Semarang city with involve 19 persons, sample was taken with purposive sampling. The result of this research shows there is improvement in control status and the spirometri was increase in asthma survivors. The conclution in his research is asthma gymnastic and breathing exercise effective to control asthma status in asthma survivor.